(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The search direction for effective training means is connected with the analysis of volleyball players’ competitive activities, which involves solving coordinationally complex motor tasks in constantly changing conditions with a severe time deficit. A wide range of factors affecting the success of game activities underscores the importance of improving the mechanisms of adaptation and restructuring of the athlete’s motor skills according to the demands of the game situation. To establish the effectiveness of a training program for developing volleyball players’ coordination abilities at the stage of specialized basic training. Theoretical analysis and synthesis of scientific and methodological literature data, pedagogical observation, pedagogical experiment, and methods of mathematical statistics. The research was conducted at the Ivan Boberskyj Lviv State University of Physical Culture and VC "Lvivyanka-LSUPC-SKIF." Control of physical and coordination training indicators of volleyball players and analysis of competitive activities were performed according to developed protocols. During the study, a significant increase in the ability to maintain static balance (p<0.05) was observed in both the experimental and control groups. Conversely, the ability to adjust and adapt motor actions in volleyball players of the experimental group significantly increased over the experiment (p<0.05), whereas the control group showed no significant changes (p>0.05). The application of pedagogical technology for coordination training contributed to a higher growth rate of most specific training indicators in the experimental group of volleyball players. Significant improvement in specific training (p<0.05) was found in almost all indicators in both groups. Building the training of volleyball players at the stage of specialized basic training with a predominant focus on developing coordination abilities allows for improving several investigated indicators chosen as criteria for coordination training. However, the degree of response to targeted pedagogical influence was different. The most dynamic indicators of coordination abilities include the accuracy of controlling spatial-temporal and dynamic movement parameters, the speed of complex reactions in choice conditions, and the indicator of specific coordination abilities. Indicators of spatial orientation, vestibular stability, and general motor experience showed somewhat lesser changes under the influence of the experimental training program.